Comprehensive study on credit programs to smallholders - María Piedad S. Geron; Gilberto M. Llanto; Jocelyn Alma R. Badiola (Philippine Institute for Development Studies (PIDS), 2016)
This paper looks at the existing credit programs for smallholders, including agrarian reform beneficiaries (ARBs). It also assesses the Agrarian Production Credit Program, which is a program being implemented in collaboration with the Department of Agriculture and the Land Bank of the Philippines for ARBs using agrarian reform beneficiary organizations as retailers. Moreover, the study determines specific gaps and issues related to meeting the credit needs of smallholders and identifies possible strategic interventions by both government and the private sector that can enhance smallholders' access to financial services.
Keywords: 330; smallholders; agrarian reform beneficiaries; landless rural workers; capacity building financial inclusion; financial literacy; innovative lending programs; wholesalers; retailers and support services